Stem cell-based therapies for silicosis: mechanisms, sources, clinical translation, and emerging strategies - Feng, Xinru; Xiao, Bo; Hou, Lixia; Zhang, Bingxi; Tian, Lincha; Mo, Biwen; Yao, Dong (Frontiers in Immunology, 2026)
Silicosis is an irreversible fibrotic interstitial lung disease triggered by chronic exposure to respirable crystalline silica (RCS). Currently, effective therapeutic interventions for this disease remain lacking, as existing clinical approaches are limited to mitigating disease progression rather than reversing or halting pathological changes. Stem cell-based therapies have emerged as a promising therapeutic modality for silicosis, leveraging their inherent biological properties to target key pathogenic cascades, such as NLRP3 inflammasome activation, TGF-β1/Smad-mediated fibrotic progression, and Th1/Th2 immune homeostasis imbalance. Notably, mesenchymal stem cells (MSCs) have advanced to early-phase (I/II) clinical trials for related pulmonary fibrotic diseases, demonstrating preliminary safety and potential for stabilizing lung function. This review synthesizes the latest advancements in stem cell-based therapeutic strategies for silicosis, with a systematic comparison of three key cell sources. The discussion encompasses adult stem cells, such as the readily accessible and immunomodulatory mesenchymal stem cells (MSCs) and the epithelium-regenerative airway basal stem cells (ABSCs), as well as the pluripotent but ethically debated induced pluripotent stem cells (iPSCs). Additionally, this review discusses critical challenges impeding the clinical translation of these therapies, including the standardization of GMP-compliant production processes, suboptimal homing efficiency of transplanted stem cells within the fibrotic pulmonary microenvironment, and inherent safety risks. Finally, this review highlights innovative translational strategies—such as CRISPR-engineered stem cells, stem cell-driven nano-delivery systems, and alveolar organoid models—and underscores the future potential of combination therapies and targeted approaches for silicosis-associated comorbidities. By integrating current knowledge, analyzing translational barriers, and exploring these forward-looking directions, this review aims to provide both theoretical insights and practical guidance for advancing the development and clinical application of stem cell-based therapies for silicosis.